Type III Monteggia Injury With Ipsilateral Distal Forearm Fracture in a Child: A Case Report - Gao, Chao; Sun, Jing Hua; Zheng, Hua Jiang; Wu, Yong Yao; Cao, Jin (Frontiers in Pediatrics, 2022)
Monteggia's fracture is a fracture of the upper 1/3 of the ulna combined with a dislocation of the radial head. It often occurs in children and adolescent. It is a combined injury. The distal forearm fracture is one of the common traumatic diseases in children, and its incidence is relatively high, accounting for about 32.9% of children's fractures, and the peak incidence is 9.9 years old[1]. However, distal forearm fractures are rarely reported to be related to Monteggia fractures. We report on a 9-year-old boy who was diagnosed with a type III Monteggia fracture with a distal forearm fracture. He underwent surgery. Rehabilitation training was performed one month after the operation. Followed up for 1 year, the affected limb functioned well, and there was no sign of radial head dislocation.